Corporate Brand Management: A Case Study of Punjab Chemicals & Crop Protection Limited (PCCPL) - Singh, Karamjeet (Indian Journal of Marketing, 2010)
The World Bank Report 2007 on agriculture titled ’Agriculture for Development’ says that greater investment in agriculture in transforming economies like India is vital for the welfare of 600 million rural poor living in these countries, mostly situated in Asia. In transforming economies such as India and China, agriculture contributed an average of 7 percent to growth in GDP between 1995 and 2003. The Agriculture sector accounts for about 13 per cent of the economy and employs just over half of the labour force. The report recommends that in these countries, where 2.2 billion people live in the countryside, agriculture agenda should focus on reducing the disparity between rural and urban incomes and raising the incomes of the rural poor.